Neoansamycins from Streptomyces sp. LZ35. Issue 56 (17th July 2017) - Liu, Mengyujie; Lu, Chunhua; Tang, Ruocong; Li, Shanren; Wang, Haoxin; Shen, Yuemao
Abstract : Neoansamycins D–I with unusual extender units and diverse post-PKS modifications were isolated from the Streptomyces sp. SR201 nam1 OE strain. Abstract : Previously, activation of the cryptic nam gene cluster led to three new naphthalenic ansamycins with unprecedented n -pentyl and n -butyl side chains from the mutant Streptomyces sp. SR201 nam1 OE strain. In this study, we further characterized the products of the mutant strain and six new neoansamycin congeners, namely neoansamycins D–I (1–6 ), were elucidated. Among them, compounds1–3 feature the conserved skeleton of neoansamycins B and C but with n -hexyl side chains, and4–6 are modified neoansamycins with n -pentyl side chains, illustrating the biosynthetic plasticity and diverse post-PKS modifications of neoansamycins.